Comparative Evaluation of 2-Port Laparoscopic Ovariectomy Using LigaSure versus Standard 3-Port Laparoscopic Ovariectomy with a Bipolar Electrode in Mares - Mohamed W. El-Sherif; Ahmed Fotouh; Ahmed N. El-Khamary (International Journal of Equine Science, 2024)
Ensuring fast and efficient hemostasis is crucial for achieving optimal outcomes in laparoscopic ovariectomy surgery. This study compared the clinical outcomes of standing laparoscopic ovariectomy for medium-sized granulosa cell tumors (≤15 cm in size) using a 2-port LigaSure versus a 3-port bipolar electrode, focusing on operating time, mean blood loss, intraoperative and postoperative complications, and the duration of the prospective hospital stay. Twelve mares were divided into two groups: six underwent standing laparoscopic ovariectomy with LigaSure through a 2-port approach, while the remaining six underwent the standard 3-port procedure with the bipolar electrode. Our findings demonstrated that 2-port laparoscopic ovariectomy using LigaSure was not only technically feasible and safe but also offered several advantages, including shorter operating times, simplified procedures, decreased postoperative analgesic requirements, and improved cosmetic appearance of surgical wounds. Moreover, this technique proved to be a reliable method for achieving hemostasis of the mesovarium while also being technically straightforward, time-saving, and cost-effective. Overall, our study suggests that 2-port laparoscopic ovariectomy with LigaSure is a promising alternative to the standard 3-port approach. This approach not only benefits patients by potentially reducing postoperative discomfort and enhancing recovery but also provides advantages for surgeons in terms of efficiency and resource utilization.